Flavonoid combinations cause synergistic inhibition of proinflammatory mediator secretion from lipopolysaccharide-induced RAW 264.7 cells. - Harasstani, Omar A.; Moin, Saidi; Tham, Chau Ling; Liew, Choi Yi; Ismail, Norazren A.; Rajajendram, Revathee; Harith, Hanis Hazeera; Zakaria, Zainul Amiruddin; Tengku Mohamad, Tengku Azam Shah; Sulaiman, Mohd Roslan; Israf Ali, Daud Ahmad (Springer Verlag, 2010)
Objectives: We evaluated several flavonoid combinations for synergy in the inhibition of proinflammatory mediator synthesis in the RAW 264.7 cellular model of inflammation.